Injúria miocárdica avaliada pela ecocardiografia de strain em pacientes após COVID-19 - Fontes, Almir Fernando Loureiro (2022)
Introduction: The SARS-COV-2 pandemic started in China at the end of 2019 and in a short time it became the main agenda of global health. Many studies have been developed to make it possible to understand the dynamics of this new disease and have shown that COVID-19 infection can cause direct and indirect damage to the heart muscle, making the investigation and clarification of this topic a fundamental item. Two-dimensional and strain echocardiography are useful tests for analyzing functional aspects of the myocardium in patients hospitalized for COVID-19. Objective: to verify the role of strain echocardiography in the identification of heart involvement in moderate and severe clinical cases of COVID-19. Method: Two-dimensional and strain echocardiography was performed 3 months after hospital discharge in patients diagnosed with COVID-19 who evolved with moderate or severe clinical forms and were treated in a public hospital in Minas Gerais/Brazil from March to August 2021. Initially, 123 patients were identified. After applying the inclusion and exclusion criteria, 89 patients were selected. To better characterize the clinical course, we also identified those who had measured fibrin D-dimer in the acute phase of the disease. A total of 72 patients remained in the sample, of which 36 had initially evolved with D-dimer elevation. Of these, 42 attended for the transthoracic and strain echocardiogram, being 23 from the group with this elevated biomarker. Epidemiological and clinical data were also analyzed. Results:. The mean age of the patients was 38.9 years, with a predominance of males. Two-dimensional echocardiography showed normal left and right ventricular systolic and diastolic functions. The 4C strain was altered in 17 patients (40%), the 2C in 16 (24.7%) and the 3C in 15 (35.7%). The global strain was altered in 20 (47.6%) patients. The variables weight, sex and presence of comorbidities showed a significant relationship with the changes identified in the strain. Conclusion: Strain echocardiography is useful in the cardiological evaluation at three months after hospital discharge due to COVID-19 as it allows the identification of myocardial impairment that is not identified on conventional echocardiography.